2019
DOI: 10.1002/admt.201900079
|View full text |Cite
|
Sign up to set email alerts
|

From Microbial Fuel Cells to Biobatteries: Moving toward On‐Demand Micropower Generation for Small‐Scale Single‐Use Applications

Abstract: Microbial fuel cells (MFCs) that generate electricity generation from a broad diversity of biomass and organic substrates through microbial metabolism, have attracted considerable research interest as an alternative clean energy technology and energy-efficient wastewater treatment method. Despite encouraging successes and auspicious pilot-scale experiments of the MFCs, increasing doubts about their viability for practical large-scale applications are being raised. Low performance, expensive core parts and mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 280 publications
(316 reference statements)
0
25
0
Order By: Relevance
“…In this process, typically metal oxides or even polarized electrodes take the role of terminal-end electron acceptors instead of oxygen. EET is important for a wide variety of industrial applications including energy generation via microbial fuel cells (MFCs), [1] biobatteries, [2] and whole cell-based biophotovoltaic cells (BPVCs), [3] storing electrical energy in chemical bonds (microbial electrosynthesis), [4] detection of analytes, [5,6] or even cost-efficient preparation of graphene from graphene oxide [7] in microbial electrochemical systems (MESs). [8] From the perspective of human health, EET has recently been implicated in colonization of the human gut by pathogenic bacteria.…”
Section: Doi: 101002/advs202000641mentioning
confidence: 99%
“…In this process, typically metal oxides or even polarized electrodes take the role of terminal-end electron acceptors instead of oxygen. EET is important for a wide variety of industrial applications including energy generation via microbial fuel cells (MFCs), [1] biobatteries, [2] and whole cell-based biophotovoltaic cells (BPVCs), [3] storing electrical energy in chemical bonds (microbial electrosynthesis), [4] detection of analytes, [5,6] or even cost-efficient preparation of graphene from graphene oxide [7] in microbial electrochemical systems (MESs). [8] From the perspective of human health, EET has recently been implicated in colonization of the human gut by pathogenic bacteria.…”
Section: Doi: 101002/advs202000641mentioning
confidence: 99%
“…For the cathode, a silver-based mixture was prepared by adding 100 mg of Ag 2 O to 2 mL of the conductive ink. Our previous works have demonstrated that, compared to the widely used potassium ferricyanide and air-cathode used in the preparation of cathodes in MFCs, Ag 2 O showed greater power performance and provided more versatile device design [13,18]. The mixture was sonicated and vortexed before pipetting it onto the cathode reservoir ( Figure 2b).…”
Section: Test Setup and Analysismentioning
confidence: 99%
“…Among them, light‐induced plant bioelectrogenesis has been studied . In addition, there have been several studies on the bioelectric generation from microbial fuel cell (MFC) which generates electrical energy through the oxidation of biodegradable organic matter . For example, harvesting energy from fermented microalgal residue using MFC which produced highest amount of energy and maximum power density compared with other MFCs has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, there have been several studies on the bioelectric generation from microbial fuel cell (MFC) which generates electrical energy through the oxidation of biodegradable organic matter. [4][5][6][7][8] For example, harvesting energy from fermented microalgal residue using MFC which produced highest amount of energy and maximum power density compared with other MFCs has been reported. [7] Also the cochlea in the inner ear of guinea pig which could induce electrical potential energy of 70-100 mV from the thin wall between the endolymph fluid in the cochlear duct and the perilymph has been reported.…”
Section: Introductionmentioning
confidence: 99%